Pengaruh Gaya Kepemimpinan, Iklim Organisasi dan Insentif terhadap Produktivitas Karyawan di PT SAI APPAREL INDUSTRIES - Adilla Farhana; Rauly Sijabat; Ratih Hesty Utami (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Employee work productivity is a hot issue and there will be no end to discuss it. Problems related to productivity are also strategic issues for companies that are programming human resources. There are many internal and external aspects that support the creation of effective and efficient work productivity in corporate culture. The purpose of this study was to determine the effect of leadership style, organizational climate and incentives on the productivity of employees of PT Sai Apparel Industries. The approach used in this research is the quantitative approach. The results of this study are leadership style, organizational climate have a positive and significant impact on employee productivity. In addition, incentives have a negative and insignificant effect on employee productivity.